Assessing the Risk of Birth Defects Associated with Exposure to Fixed-Dose Combined Antituberculous Agents during Pregnancy in Rats - O. Awodele; E. B. Patrick; Esther Oluwatoyin Agbaje; A. A. Oremosu; S. C. Gbotolorun (The Scientific World Journal)
Due to the risks of disease progression and transmission to the newborn, treatment of tuberculosis is often pursued during pregnancy and fixed-dose combined antituberculous agents have been found to be beneficial. Unfortunately, there is paucity of data on the safety of the fixed-dose combined antituberculous drugs during pregnancy. This study intends to assess the teratogenic effect of fixed-dose combined antituberculous drugs on the organogenesis stage of fetal development and also investigate the possible roles of vitamin C in modulating the teratogenic effects of these agents on the fetus using animal model. Pregnant rats were divided into 3 groups with 12 animals per group: group 1 received distilled water (10 mL/kg) orally; group 2 received 51.4 mg/kg/day of fixed-dose combined antituberculous agents orally; group 3 received 51.4 mg/kg/day of fixed-dose combined antituberculous agents plus vitamin C (10 mg/kg/day) orally. Six rats in each group were randomly selected and sacrificed on day 20 by cervical dislocation prior to day 21 of gestation, and the foetuses were harvested through abdominal incision for physical examination. Blood samples were collected from the 1st filial rats of the remaining six animals for biochemical and hematological examination. The liver, kidney, heart, and brain of all the sacrificed animals were used for histopathological examination. There were significant (𝑃≤0.05) low birth weights of the foetuses of the animals that were treated with fixed-dose combined antituberculous agents. The haematological parameters also revealed a reduction in the platelets counts and neutrophiles at the first filial generation. Significant (𝑃≤0.05) elevations in the levels of aspartate aminotransferase (AST) and alkaline phosphatase (ALP) in the foetuses of the animals treated with fixed-dose combined antituberculous agents were also observed. However, the combination of vitamin C with fixed-dose combined antituberculous agents significantly (𝑃≤0.05) reduced the level of AST. Fixed-dose combined antituberculous agents have teratogenic potential as shown in low birth weight and mild liver damage in the first filial of the treated animals. As much as it is imminent to treat TB patients in pregnancy, there is need to always exercise caution and clinically weigh the risk-benefit ratio.